36. Thực trạng hoạt động thể lực và một số yếu tố liên quan của sinh viên y năm thứ nhất Trường Đại học Y Phạm Ngọc Thạch - Anh, Hà Võ Vân; Đăng, Vũ Khắc Minh; Trinh, Nguyễn Thị Ngọc (Tạp chí Nghiên cứu Y học, 2025)
The World Health Organisation (WHO) has recommended physical activity (PA) to improve physical and mental health outcomes in adults. Studies at Hai Phong University of Medicine and Pharmacy and Hanoi Medical University have shown a relatively high proportion of students, including those in health-related fields, do not engage in sufficient physical activity according to WHO recommendations 1,2. This study aimed to determine the prevalence of first-year medical students at Pham Ngoc Thach University of Medicine meeting PA recommended by the WHO and associated factors, using the Global Physical Activity Questionnaire (GPAQ). It was a cross-sectional study of 281 students in 2023. Logistic regression analyses were performed to determine associated factors with meeting recommended PA. The proportion of students meeting recommended PA was 67.62%. Students who self-rated their health as good had 2.03 times higher odds of meeting recommended PA levels (95% CI: 1.14–3.61). Sedentary time and average daily sleep duration were inversely dose-response associated with meeting PA recommendations (p<0.001). Therefore, targeted interventions are needed to enhance awareness of PA benefits for health among university students.